Does Higher Oil Prices Influence Renewable Energy Consumption? A Cross-sectional Approach - Farouq, Ibrahim; Sulong, Zunaidah (International Journal of Membrane Science and Technology, 2023)
One of the most effective strategies to mitigate global warming is to reduce the use of fossil fuels in the generation of energy. Thus, transitioning to renewable energy is critical to long-term sustainable growth. One of the Sustainable Development Goals of United Nations is to transition towards renewable energy. But many resource-rich economies are faced with numerous barriers towards the transformation process. In this regard, we examine the effect of increased oil prices, income, information communication technology, and financial development on renewable energy consumption in some OPEC member nations from 1980 to 2020. The findings shows that oil price has a negative effect on renewable energy consumption. While information communication technology moderates the relationship between financial development and renewable energy consumption. Therefore, A green finance system helps a country to build an ecologically sound renewable energy system, which greatly stimulates the usage of renewable energy. Green financial institutions should be formed in all sample nations to encourage financial activity and support environmentally beneficial projects.